Plasminogen is a critical regulator of cutaneous wound healing - Sulniute, Rima; Shen, Yue; Guo, Yong-Zhi; Fallah, Mahsa; Ahlskog, Nina; Ny, Lina; Rakhimova, Olena; Broden, Jessica; Boija, Hege; Moghaddam, Aliyeh; Li, Jinan; Wilczynska, Malgorzata; Ny, Tor (Thrombosis and Haemostasis, 2016)
Wound healing is a complicated biological process that consist of partially overlapping inflammatory, proliferation and tissue remodelling phases. A successful wound healing depends on a proper activation and subsequent termination of the inflammatory phase. The failure to terminate the inflammation halts the completion of wound healing and is a known reason for formation of chronic wounds. Previous studies have shown that wound closure is delayed in plasminogendeficient mice, and a role for plasminogen in dissection of extracellular matrix was suggested. However, our finding that plasminogen is transported to the wound by inflammatory cells early during the healing process, where it potentiates inflammation, indicates that plasminogen may also have other roles in the wound healing process. Here we report that plasminogen-deficient mice have extensive fibrin and neutrophil depositions in the wounded area long after re-epithelialisation, indicating inefficient debridement and chronic inflammation. Delayed formation of granulation tissue suggests that fibroblast function is impaired in the absence of plasminogen. Therefore, in addition to its role in the activation of inflammation, plasminogen is also crucial for subsequent steps, including resolution of inflammation and activation of the proliferation phase. Importantly, supplementation of plasminogen-deficient mice with human plasminogen leads to a restored healing process that is comparable to that in wild-type mice. Besides of being an activator of the inflammatory phase during wound healing, plasminogen is also required for the subsequent termination of inflammation. Based on these results, we propose that plasminogen may be an important future therapeutic agent for wound treatment.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Plasminogen; wound healing; inflammation